2020
DOI: 10.2298/jsc190715109k
|View full text |Cite
|
Sign up to set email alerts
|

Binuclear copper(II) complexes: Synthesis, structural characterization, DNA binding and in silico studies

Abstract: Two new binuclear Cu(II) complexes represented by the general formula {(dmso)Cu(µ-L)4Cu(dmso)} (1) and {(Phen)(L)Cu(µ-L)2Cu(L)(Phen)} (2) where dmso = dimethyl sulphoxide, L = 2-bromophenyl acetate and Phen = 1,10-phenanthroline have been synthesized, isolated quantitatively and characterized by UV/Visible and FT-IR spectroscopic techniques, Thermogravimetry/Differential Thermal Analysis and X-ray single crystal XRD studies. Complex 1 is paddlewheel with 1,2-O,O-bridging while 2 has 1,1-O-bridging. The values … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…2.8 × 10 5 and 2.6 × 10 6 M −1 , respectively (note: K app = K e × 12.6/ C 50 , where K e = 9.5 × 10 6 M −1 and C 50 is the concentration of test compounds required to reduce the EtBr fluorescence by half). The binding constants are in line with a number of Cu(II)-phenanthroline systems previously reported [ 36 ] and it should also be noted that the influence of charge may play a role in the higher binding affinity associated with the Cu-phendione complex, which carries a 2+ cationic charge. Furthermore, the binding constant of Cu-phendione is similar to that identified for the minor groove binding agent netropsin tested under similar conditions but is an order of magnitude lower that actinomycin D (Table 1 ) [ 33 ].…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…2.8 × 10 5 and 2.6 × 10 6 M −1 , respectively (note: K app = K e × 12.6/ C 50 , where K e = 9.5 × 10 6 M −1 and C 50 is the concentration of test compounds required to reduce the EtBr fluorescence by half). The binding constants are in line with a number of Cu(II)-phenanthroline systems previously reported [ 36 ] and it should also be noted that the influence of charge may play a role in the higher binding affinity associated with the Cu-phendione complex, which carries a 2+ cationic charge. Furthermore, the binding constant of Cu-phendione is similar to that identified for the minor groove binding agent netropsin tested under similar conditions but is an order of magnitude lower that actinomycin D (Table 1 ) [ 33 ].…”
Section: Resultssupporting
confidence: 89%
“…Hydrophobic interactions were only observed between Cu-phendione and DNA molecules. Kamran et al [ 36 ] have applied computational methods to investigate the interaction of DNA and binuclear Cu(II) complexes represented by the general formula {(DMSO)Cu(µ-L) 4 Cu(DMSO)} and {(1,10-phen)(L)Cu(µ-L) 2 Cu(L)(1,10-phen)}, where L = 2-bromophenyl acetate. It was observed that both binuclear Cu(II) complexes formed H–π interaction with adenine and guanine residues of the DNA [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Copper(II) complexes have been considered and suggested to be better candidates for cancer treatment due to their significant role in biological systems, having negligible or no side effects [14,15]. Mononuclear copper(II) complexes with the phenanthroline type of ligand show lesser affinities to DNA binding compared to binuclear copper(II) complexes [16,17]. In angiogenesis, copper appears to be involved in stimulating proliferation and endothelial cell migration, and acts as a cofactor for angiogenic factors (VEGF, bFGF, TNF-α, and IL-1) [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%